Assessment of the Sustainable Development of a Tourism Destination: The Case of an Adventure Park - Papečkys, Saulius (Vilnius University Proceedings, 2023)
The sustainable development of a tourism destination is a process that is continuously improved and has long-term value. By applying and distributing the economic, social and cultural dimensions equally, it is possible to achieve well-being for the environment and local people not only now, but also in the future. The study showed that the sustainable development of a tourism destination is presented differently by each of the authors, but all of them convey the idea that it is a process that includes economy, environmental protection, social dimensions and their management. By applying the process of sustainable development, tourism destinations achieve economic benefits without harming the environment and taking into account the social and cultural well-being of local people. It is recommended that voluntary publicity of environmental and socio-cultural activities in a tourism destination is an important factor that improves the image and increases value in society. Sustainability management is a more comprehensive, constructive, holistic approach than the management systems offered so far